Limitations of empirical therapy for bacterial meningitis in a healthy child with Listeria monocytogenes meningitis - Elder, Charlotte J.; Urquhart, Donald S. (Journal of Pediatric Neurology, 2006)
Whilst Listeria monocytogenes (L. monocytogenes) meningitis is more common in neonates and the immunosuppressed, consideration of listeriosis is also warranted in otherwise healthy children. We present a case of L. monocytogenes meningitis in an immunocompetent 6-year-old girl. She presented with fever, irritability, pain on neck flexion and signs of a left-sided hemiplegia. Cerebrospinal fluid analysis showed hypoglycorrhachia and raised protein, as well as a pleocytosis with lymphocyte predominance. Standard empirical therapy for meningitis, utilising a third-generation cephalosporin with or without vancomycin would fail to cover L. monocytogenes. Therefore, in cases of meningitis where focal neurological signs are present, consideration should be given to the use of ampicillin or meropenem as part of first-line therapy.
Keywords: Meningoencephalitis; hypoglycorrhachia; cerebrospinal fluid pleocytosis; Listeria monocytogenes